Pengaruh Tabungan Dan Deposito Terhadap Rentabilitas (Studi Empiris Pada Perbankan Yang Terdaftar Di BEI Tahun 2020-2022) - Winda Anastasya Butar Butar; Ndruru, Laurensia Konstantia; Sitorus, Tessalonika Bertuah; Hutapea, Veby Elfrida; Hasugian, Christnova; Siallagan, Hamonangan (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This research was conducted to determine the effect of savings and deposits on profitability in banks listed on the Indonesia Stock Exchange in 2020-2022. In this research, the data used is secondary data, data obtained not from direct research on an object but data that is available on the IDX in the form of annual financial reports from the banking sector for the period 2020 - 2022, the appropriate sample for use is 7 banks. The formulation of the problem in this research is whether savings and deposits have an effect on profitability in banks listed on the Indonesia Stock Exchange from 2020 - 2022. The analysis technique used in this research is Purposive Random Sampling, namely a sampling technique based on selected groups according to characteristics. -special characteristics possessed by the sample. The results of the t test show that the independent variable, namely the deposit variable, has a significant influence on profitability, while the savings variable has no significant influence on profitability. Simultaneous test results show that savings and deposits together have a significant effect on profitability in banks listed on the Indonesia Stock Exchange from 2020-2022. The results of the coefficient of determination test show an Adjusted R Square value of 0.615, this means that 61.5% of the dependent variable can be explained by the independent variable, while the remaining 39.5% is explained by other factors not examined in this research.